DEVELOPING THE WRITING PARAGRAPH THROUGH QUICKWRITING FOR JUNIOR HIGH SCHOOL AT SMP SWASTA PAHLAWAN NASIONAL - Natasya Lia Aldilla Sitorus Pane; Sumarsih Sumarsih; Tiarnita Maria Sarjani Br. Siregar (Universitas Negeri Medan, 2018)
This study deals with developing the writing paragraph through quickwriting for junior high school at smp swasta pahlawan nasional. The objectives of this study were to find out to improve the students’ ability in writing paragraph of grade VIII students by using quickwriting strategy. Data data of the research was taken from the secondary grade of Junior High School Students at SMP Swasta Pahlawan Nasional Medan, which is taken from one class, contain 33 student. The data in this research collected by using interview and questionnaire. The interview and questionnaire will be given to collect the students’ need, problem and interesting in learning English, particularly in writing and using quick writing in teaching and learning. In the teaching-learning process the teacher should prepare before conducting the lesson. The first is classroom procedures in teaching-learning process. Classroom procedures used by English teacher are opening, quickwriting, main activities (exploration-elaboration-confirmation), closing. There are some problems faced in the teaching-learning process. The problems faced are problem in developing idea, organizing idea, difficulties in vocabulary, tenses, and grammar, different capability of the students, and limited time. The consequently, the teacher should give solutions to cope the problems faced in teaching-learning process. So, the teacher should be creative to minimize the problem faced in teaching-learning process in order to make the students enjoy with the materials and develop student’s ability. Keywords : writing paragraph, quickwriting